2004
DOI: 10.1080/01443610310001620242
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of pregnancy after large loop excision of the transformation zone of the cervix

Abstract: A retrospective case control study to assess the outcome of pregnancy after large loop excision of the transformation zone of cervix (LLETZ) was carried out. One hundred and nineteen women who had undergone LLETZ and delivered in Basildon District Hospital were identified between January 1995 and December 1998; 119 age- and parity-matched controls were selected. Variables included were miscarriages, preterm deliveries, gestation at delivery, onset of labour, length of labour, augmentation of labour, mode of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 7 publications
0
27
0
2
Order By: Relevance
“…We confirmed that treatment does not increase the risk of cesarean delivery. 2,3,6,7,9,10,12 However, there is conflicting evidence about the risk of LBW and perinatal mortality and morbidity. 2-4,6 -10,12,13 Although the risk of these does not differ in women with or without CIN3 or in those treated by excision or ablation, we found an increased risk of perinatal mortality and morbidity in those women who had no treatment, indicating common risk factors between women who default to treatment and those who are at increased risk of poor obstetric outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We confirmed that treatment does not increase the risk of cesarean delivery. 2,3,6,7,9,10,12 However, there is conflicting evidence about the risk of LBW and perinatal mortality and morbidity. 2-4,6 -10,12,13 Although the risk of these does not differ in women with or without CIN3 or in those treated by excision or ablation, we found an increased risk of perinatal mortality and morbidity in those women who had no treatment, indicating common risk factors between women who default to treatment and those who are at increased risk of poor obstetric outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Other concerns regarding LEEP include risk of cesarean delivery (owing to failed cervical dilatation), low birth weight (LBW), and perinatal mortality and morbidity. [2][3][4][5][6][7][8][9][10][11][12] Results of existing studies on reproductive outcomes after treatment for CIN 2-18 are conflicting. All are retrospective observational studies, and most are underpowered to provide conclusive evidence on the effect of LEEP on spontaneous preterm delivery.…”
mentioning
confidence: 99%
“…For outpatient LLETZ procedures, a short-term complication rate of just under 10% has been reported in one study in the United States, but the rate of major complications was 0.6% [42]. Studies of pregnancy outcome after loop excision have had inconsistent results, and it is difficult to exclude potential confounding by genital infection, type of transformation zone, and extent of treatment [43][44][45]. Although a single LLETZ is unlikely to impair reproductive function, there are increasing concerns with repeated procedures.…”
Section: Current Evidence On Effectiveness Of Cytologic Surveillance mentioning
confidence: 95%
“…This could be a reflection of the uncertainty induced by earlier studies, which were unclear about the effect of these treatments on pregnancy outcome and subsequent risk of preterm delivery [13][14][15][16] or could be reservations regarding the design of some of the earlier studies [6]. Thirty-six per cent of the respondents would routinely perform cervical assessment on women with excisional treatment of cervix, and 14 respondents outlined the conditions to perform the assessment (Table 3).…”
Section: Discussionmentioning
confidence: 98%